Low Ten-eleven-translocation 2 (TET2) transcript level is independent of TET2 mutation in patients with myeloid neoplasms. Issue 1 (December 2016) - Scopim-Ribeiro, Renata; Machado-Neto, João; de Melo Campos, Paula; Niemann, Fernanda; Lorand-Metze, Irene; Costa, Fernando; Olalla Saad, Sara; Traina, Fabiola
Abstract Background New sequencing technologies have enabled the identification of mutations inTen-eleven-translocation 2 (TET2 ), an enzyme that catalyzes the conversion of 5-methylcytosine into 5-hydroxymethylcytosine (5-hmC) in myeloid neoplasms. We have recently identified reducedTET2 mRNA expression in myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML), which is associated with a poor overall survival in MDS. We herein aimed to investigateTET2 mutations and their impact onTET2 expression in a cohort of patients with myeloid neoplasms, including MDS and AML patients. Findings TET2 mutations were observed in 8 out of 19 patients (42 %) with myeloid neoplasms. TheTET2 expression profile was similar between in wild type and inTET2 mutated patients. Conclusion Our results suggest thatTET2 expression is reduced in MDS/AML patients, independently of mutational status.